Off-pump coronary artery bypass grafting improves short-term outcomes in high-risk patients compared with on-pump coronary artery bypass grafting: Meta-analysis - Kowalewski, Mariusz; Pawliszak, Wojciech; Malvindi, Pietro Giorgio; Bokszanski, Marek Pawel; Perlinski, Damian; Raffa, Giuseppe Maria; Kowalkowska, Magdalena Ewa; Zaborowska, Katarzyna; Navarese, Eliano Pio; Kolodziejczak, Michalina; Kowalewski, Janusz; Tarelli, Giuseppe; et al. (The Journal of thoracic and cardiovascular surgery, 2016)
To assess the benefits and risks of off-pump coronary artery bypass (OPCAB) versus coronary artery bypass grafting (CABG) through a meta-analysis of randomized controlled trials (RCTs), and to investigate the relationship between outcomes and patient risk profile. PubMed, Embase, the Cumulative Index of Nursing and Allied Health Literature, Scopus, Web of Science, Cochrane Library, and major conference proceedings databases were searched for RCTs comparing OPCAB and CABG and reporting short-term (≤30 days) outcomes. Endpoints assessed were all-cause mortality, myocardial infarction (MI), and cerebral stroke. The meta-analysis included 100 studies, with a total of 19,192 subjects. There was no difference between the 2 techniques with respect to all-cause mortality and MI (odds ratio [OR], 0.88; 95% confidence interval [CI], 0.71-1.09; P = .25; I2 = 0% and OR, 0.90; 95% CI, 0.77-1.05; P = .19; I2 = 0%, respectively). OPCAB was associated with a significant 28% reduction in the odds of cerebral stroke (OR, 0.72; 95% CI, 0.56-0.92; P = .009; I2 = 0%). A significant relationship between patient risk profile and benefits from OPCAB was found in terms of all-cause mortality (P < .01), MI (P < .01), and cerebral stroke (P < .01). OPCAB is associated with a significant reduction in the odds of cerebral stroke compared with conventional CABG. In addition, benefits of OPCAB in terms of death, MI, and cerebral stroke are significantly related to patient risk profile, suggesting that OPCAB should be strongly considered in high-risk patients.